Night moves (1975) [videorecording (DVD)] - Penn, Arthur, 1922-2010; Hackman, Gene; Warren, Jennifer, 1941-; Clark, Susan, 1940- (Warner Home Video, 2005)
A self-styled detective scrounging a living out of divorce actions, missing persons, and runaway kids finally gets his first big case. Unraveling his mystery, he's always one step behind.